Overview of Public Knowledge About Malaria Treatment in Matungkas Village of Dimembe District of North Minahasa Regency - Tryastuti Paula Andini Abast (UNIVERSITAS SAM RATULANGI, 2023)
Malaria is a disease caused by protozoan parasite of the genus. Plasmodium that is naturally transmitted through the bite of a female Anopheles mosquito. Until now, malaria is still a major problem in world health glasses. This research ains to find out the public's knowledge about malaria, with preventive behavior and ways of treatment of malaria. This research uses observational study research design and with a Cross-sectional approach. The population obtained as many as 76 samples. Data collection in this study using questionnaires. Based on questionnaire data, from the characteristics of respondents obtained, the following results were obtained: The level of public understanding of malaria treatment is quite large, which is 75%, then the level of public understanding of the spread of moderate malaria is 51.3%, then the level of public understanding of malaria prevention is high level of 61.8%. Based on these three data, it can be said that public knowledge about Malaria is 50% high level and 50% low level.